The Future of Customized Education in Edutech through Digital Innovation - 구효진; 박진영 (International Journal of Advanced Culture Technology(IJACT), 2024)
Digital technologies such as Fifth-Generation Mobile Communications (5G), Virtual Reality (VR), and Augmented Reality (AR) are driving transformative innovations across various industries, with education being a particularly notable area of impact. These technological advancements are fostering the expansion of EduTech and digital big data, thereby enabling the provision of highly personalized and accessible learning experiences. By integrating Artificial Intelligence (AI), blockchain, and Extended Reality (XR) technologies, educational methodologies are becoming increasingly immersive, adaptive, and efficient. These innovations are redefining traditional learning paradigms, enhancing learner engagement, and broadening global access to education. Governments and institutions worldwide are making substantial investments in the digitalization of educational environments, utilizing state-of-the-art tools to optimize learning outcomes and prepare learners for the challenges of the future. We examine the profound implications of digital innovation on education, focusing on its role in shaping new paradigms of learning and exploring its broader socio-economic impacts.